What Patients Bring to the Medical Encounter: Dealing With the Whole Patient - Monica Lypson; Rachel Perlman; Caren Stalburg; Christa Johnston; Robert Lash; Paula Ross (Association of American Medical Colleges, 2010)
Abstract Introduction The overall objective of this case is to provide students with an opportunity to focus on the important aspects of a patient's social history and how it relates to the current medical issues at hand. In this session we focus on their skills in obtaining adequate and useful information about the social context of a patient with limited English proficiency in the medical interview. Methods The case contains three components. Prior to the session students complete a series or required readings and complete a written assignment to promote self-directed learning and reflection in the area of social determinants of health. This assignment is then submitted to the facilitator for review. Once the session begins the students explore the case of Ms. Vlas, a theoretical patient. Finally the students discuss patient follow-up, again in small groups. Results Second-year medical students found the case moderately valuable. Students were comfortable discussing their reactions to the cases and the topics associated with Ms. Vlas in the small-group setting. Discussion This has been found to help medical students understand the role physicians have in caring for patients with limited English proficiency.